Lipidomic landscape of lipokines in adipose tissue derived extracellular vesicles - Zhang, Yan; Dong, Tingyan; Wang, Muyao (Frontiers in Molecular Biosciences, 2023)
Adipose tissue-derived extracellular vesicles (EVs-AT) are recognized as critical mediators of metabolic alterations in obesity-related diseases. However, few studies have focused on the role of lipids within EVs-AT in the development of obesity-related diseases. In this study, we performed a targeted lipidomic analysis to compare the lipidome of EVs secreted by inguinal white adipose tissue (EVs-iWAT), epididymal white adipose tissue (EVs-eWAT), and interscapular brown adipose tissue (EVs-BAT) in lean and obese mice. We uncovered a comprehensive lipidomic map, revealing the diversity and specific lipid sorting in EVs-iWAT, EVs-eWAT, and EVs-BAT in obesity. Biological function analyses suggested that lipids encapsulated within EVs-AT of obese individuals might correlate with metabolism, pro-inflammatory response, and insulin resistance. These effects were particularly pronounced in EVs-eWAT and EVs-BAT. Our findings indicated that EVs-AT serves as novel carriers for lipokines, thereby mediating the biological functions of EVs-AT. This study holds promise for the identification of new biomarkers for obesity-related diseases and the development of new strategies to combat metabolic diseases.